Design, synthesis, molecular modeling and anti-hyperglycemic evaluation of quinazolin-4(3H)-one derivatives as potential PPARγ and SUR agonists. Issue 17 (1st September 2017) - Ibrahim, Mohamed K.; Eissa, Ibrahim H.; Alesawy, Mohamed S.; Metwaly, Ahmed M.; Radwan, Mohamed M.; ElSohly, Mahmoud A.
Graphical abstract: Highlights: Twenty compounds of novel quinazolin-4(3 H )-ones bearing sulfonylurea derivatives were designed and synthesized. Molecular docking, pharmacophore, QSAR and ADMET studies were carried out. In vivo anti-hyperglycemic activity, in vitro PPARγ binding affinity and insulin-secreting ability were carried out. Some of the synthesized compounds showed promising anti-hyperglycemic activities. Abstract: Peroxisome proliferator-activated receptor gamma (PPARγ) and sulfonylurea receptor (SUR) play crucial roles in management of type-2 diabetes mellitus. In this study, a series of novel quinazoline-4(3 H )-one-sulfonylurea hybrids were designed and synthesized as dual PPARγ and SUR agonists. The synthesized compounds were evaluated for their in vivo anti-hyperglycemic activities against STZ-induced hyperglycemic rats. Four compounds (19a, 19d, 19f and25g ) demonstrated potent activities with reduction in blood glucose levels of 40.43, 46.42, 41.23 and 42.50 %, respectively. The most active ten compounds were further evaluated in vitro for their PPARγ binding affinities and insulin-secreting abilities. Compounds19b, 19d, 19f, 25f and25g exhibited the highest affinities against PPARγ with IC50 values of 0.371, 0.350, 0.369, 0.408 and 0.353 µM, respectively. In addition, compounds19d, 19f, and25d showed the highest insulin-secreting activities with EC50 values of 0.97, 1.01 and 1.15 µM, respectively. Furthermore, molecular docking and pharmacophore generation techniques were carried out to investigate binding patterns and fit values of the designed compounds with PPARγ and SUR, respectively. Also, two QSAR models were generated to explore the structural requirements controlling the different biological activities of the synthesized compounds against PPARγ and SUR.